An Empirical Test of Weak-Form Market Efficiency in Bullish and Bearish Phases: Evidence from the LQ45 Index on the Indonesia Stock Exchange - Khujaifah, Alwi; Oktamade, Dion; Sagala, Dina Marlina; Rahmadani, Lesty; Fathoni, Israr (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
The purpose of this study is to examine the extent of weak-form market efficiency under two different market conditions: bullish and bearish, and how these conditions influence investor decision-making. Additionally, this research aims to demonstrate that investing in the capital market can offer investors reasonable and potentially promising returns. However, investor reactions to such information may vary. Differences in investors’ responses and perceptions lead to variations in stock buying and selling decisions. Similarly, stock fluctuations in the Indonesian capital market are highly volatile. A quantitative research method was employed using SPSS version 22 software, which included normality and run tests. The study utilized the LQ45 Index, one of Indonesia’s stock indices, comprising companies with high liquidity and large market capitalization. The test data were analyzed using SPSS version 22, including normality and run tests. The results of the normality tests indicate that returns during both bearish and bullish periods are not normally distributed. Furthermore, the run test results show that returns in both market conditions do not follow a random pattern, implying that the market is not weak-form efficient.